Environmental Site Characterization and Risk-Based Evaluation of a Site Contaminated with Tetrachloroethene (PCE) and Trichloroethene (TCE) - C. L. Quast; M. G. Fisher; A. H. Broughton (Journal of Hazardous Substance Research, 1999)
A healthcare company purchased property in eastern Iowa for a facility expansion. Before the purchase, a Phase I environmental site assessment (ESA) revealed that the property was the site of a former dry cleaning business. Phase II sampling and testing indicated that tetrachloroethene (PCE) and trichloroethene (TCE) had affected site soil and groundwater. Maximum concentrations of PCE and TCE in groundwater were 538 and 209 µg/L, respectively, and 105 and 1.51 mg/kg in soil. Additional sampling delineated the vertical and horizontal extent of contamination in the soil. The concentrations of the chlorinated solvents in both the soil and groundwater were below levels of regulatory concern. However, the company was concerned that the Iowa statewide standard for PCE in soil (780 mg/kg) might not provide adequate protection for several exposure pathways and wanted to assess the risk to the public from the contamination at the site. The results of a receptor survey were used to develop site-specific target levels (SSTLs) for contamination, using accepted human health exposure factors, models, and chemical-specific toxicity values. The recommended remedial options allowed the company to minimize the human health risks posed by contamination at the site.
Keywords: chlorinated; risk; dry cleaners; tetrachloroethene; trichloroethene